(3GdBKGQ GdHGbjI Yf GdbQhf GdNGdjIs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi CMO GdCOHGA Yf GdJhGQjN GdJj jSJYedgG GdCee aYdeJ Cf Pdc GeQ UYH GdeJfGhd hCHJOF aCbhd s
(3BNQgG (B:s
(3hdfNJe BNQGdcJGH HGdMeO ddg GdPi fUQ hgOi s
(3GfXQ GdbSe GdKGdK HQbe (B867s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B475 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B870 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs